21.2: Invited Paper: A Hyperspectral Imaging Radiance Colorimeter for Fast Measurement of Display. (4th October 2019) - Song, Li; Tang, Xian; Wu, Di; Pan, Jiangen
Abstract : Nowadys, there are two technical schemes suitable for the measurement of display ‐ spatial scanning and spectral scanning in hyperspectral imaging field. This paper analyzed the advantages and disadvantages of both two schemes, and proposed an improved design of hyperspectral imaging radiance colorimeter for fast measurement of display. In addition, we introduced a calibration method of hyperspectral imaging radiance colorimeter for more accurate measurements.